Perfectionism and Self-esteem in Argentine University Students - Helguera, Gisela Paola; Oros, Laura Beatriz (Pensando Psicología, 2018)
Objective: To explore the extent to which perfectionism and self-esteem are related to Argentine university students. Method: Three hundred and forty-one subjects answered the Almost Perfect Scale-Revised and the Rosenberg Self-Esteem Scale. Results: The results showed a significant, robust, negative relationship between self-esteem and perfectionist discrepancy (r = -0,53; p < 0,001), and a weak but significant relationship between selfesteem and high standards (r = 0,19; p <0,001). Also, significant differences were observed (F (2,145) = 11,89; p < 0,001, η2p = 0.14) in the self-esteem of adaptive perfectionists, compared to that of maladaptive perfectionists and non-perfectionists; adaptive perfectionists scored higher than the other two groups. Conclusions: It was established that, in line with the findings of previous studies, the dimensions of perfectionism are differentially related to self-esteem so that discrepancy is the characteristic that induces the greatest amount of variance explained. The practical importance of the results obtained justifies the incorporation of psychoeducational strategies to reduce dysfunctional perfectionism and foster adaptive perfectionism in any program whose aim is to promote self-esteem in Argentine university students.